NMOS device characteristics in electron-beam-recrystallized SOI - Meyer, Jack D., author; Fukumoto, Jay T., author; Moore, Cameron Alden, author; Collins, George J., author; Buser, James R., author; Thompson, Lance Robert, author; IEEE, publisher (Colorado State University. Libraries, 1993)
Characteristics of n-channel MOSFET's fabricated in cold cathode electron-beam-recrystallized silicon-on-oxide layers have been examined. Assorted crystallographic defects exist in the recrystallized silicon layer ranging from highly branched subgrain boundaries to widely spaced parallel subgrains and rows of threading dislocations. Some of these MOSFET transistors have characteristics approaching those fabricated in bulk silicon including = 828-cm2/V • s electron surface mobilities and 130-mV/ decade inverse subthreshold slopes. However, many of the devices tested exhibited leakage currents up to 10-6 A/µm, resulting in high inverse subthreshold slopes and reduced threshold voltages. Some effects of crystal imperfections on device behavior are discussed.
Keywords: carrier mobility; dislocations; electron beam applications; grain boundaries; insulated gate field effect transistors; leakage currents; recrystallisation annealing; semiconductor-insulator boundaries